2022
DOI: 10.1007/s10640-022-00675-0
|View full text |Cite
|
Sign up to set email alerts
|

Information, Consequentiality and Credibility in Stated Preference Surveys: A Choice Experiment on Climate Adaptation

Abstract: Information provided in valuation surveys has been shown to affect stated preferences, which in turn may matter for the validity and reliability of survey-based value estimates. Although information effects are widely documented in stated preference studies, the reasons underlying the effects are less established. We focus on information about the policy context of the valuation scenario and examine two pathways which may help explain how including such information in a survey affects stated preferences. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Including a payment vehicle as a monetary attribute in the CE design is crucial in valuing nature resources. Choosing the appropriate payment method is crucial for effectiveness and alignment of incentives in stated preference surveys, particularly in developing countries and emerging economies where traditional payment methods from developed countries may not be suitable (Welling et al 2022;Zawojska et al 2019).…”
Section: Literature Review Economic Valuation Of Natural Resourcesmentioning
confidence: 99%
“…Including a payment vehicle as a monetary attribute in the CE design is crucial in valuing nature resources. Choosing the appropriate payment method is crucial for effectiveness and alignment of incentives in stated preference surveys, particularly in developing countries and emerging economies where traditional payment methods from developed countries may not be suitable (Welling et al 2022;Zawojska et al 2019).…”
Section: Literature Review Economic Valuation Of Natural Resourcesmentioning
confidence: 99%
“…For example, perceived consequentiality will likely be weakened when a respondent does not find levels of the public good provision considered in the preference elicitation task(s) as credible (e.g., technically impossible for the actual provision; Welling, Zawojska, and Sagebiel, 2022) or is otherwise unconvinced by the way the preferences are elicited.…”
Section: Theoretical Considerations About Choosing the Location Of Co...mentioning
confidence: 99%
“…Complementing hedonic studies, several discrete choice experiments (DCE) have found positive WTP to benefit from different types of UGS such as: green walls (Collins et al, 2017;Fruth et al, 2019), green roofs (Vanstockem et al, 2018) and street trees (Giergiczny & Kronenberg, 2014;Ng et al, 2015;Soto et al, 2018;Fruth et al, 2019;Dongen & Timmermans, 2019;Mokas et al, 2021;Welling et al, 2022) or different naturalness (Bronnmann et al, 2020). These studies describe UGS with landscape attributes which include : type of land use (grassy/wooded area, presence of water, etc.…”
Section: Literaturementioning
confidence: 99%